Anti-Toxoplasma Activities of Zea Mays and Eryngium Caucasicum Extracts, In Vitro and In Vivo - Ehsan Ahmadpour; Mohammad Ali Ebrahimzadeh; Mehdi Shari; Sara Edalatian; Shahabeddin Sarvi; Mahbobeh Montazeri; Saeed Mehrzadi; Mohammad Akbari; Mohammad Taghi Rahimi; Ahmad Daryani (Korean Pharmacopuncture Institute, 2019)
Objectives: Toxoplasmosis is a worldwide health problem that caused by intracellular apicomplexan parasite, Toxoplasma gondii (T. gondii). Considering that the available drugs for toxoplasmosis have serious host toxicity, the aim of the current study was to survey the in vitro and in vivo anti-Toxoplasma activity of Zea mays (Z. mays) and Eryngium caucasicum (E. caucasicum) extracts. Methods: Four concentrations (5, 10, 25, and 50 mg mL1) of Z. mays and E. caucasicum methanolic extracts for 30, 60, 120, and 180 min were incubated with infected macrophages and then the viability of RH strain of T. gondii tachyzoites was evaluated by trypan blue staining method. Also, we evaluated the survival rate of acutely infected mice with the extracts (100 and 200 mg kg-1 day1) intraperitoneally for 5 days after infection with 2× 104 tachyzoites of T. gondii. Results: The anti-Toxoplasma effect of the methanolic extracts were extremely significant compared to the negative control group in all exposure times (P < 0.05). The Z. mays (10, 25 and 50 mg mL-1) killed 100% of the parasites after 180 and 120 min exposure, respectively. Also, high toxoplasmacidal activity was observed with E. caucasicum extract. Furthermore, treatment of experimentally infected mice with the Z. mays (100, 200 mg kg-1 day-1) and E. caucasicum (100 mg kg-1 day-1) significantly increased their survival rate compared to untreated infected control (P < 0.05). Conclusion: These extracts are promising candidates for further medicine development on toxoplasmosis. However, further investigations are necessary to clarify effective fractions of the Z. mays and E. caucasicum extracts and the mechanisms of action.